The relationship between physical motor skills, gender and relative age effects in young austrian alpine ski racers - Müller, L.; Müller, E.; Kornexl, E.; Raschner, C. (International Journal of Sports Science and Coaching, 2015)
The Relative Age Effect (RAE) refers to an over-representation of athletes born early in a selection year. The aims of this study were twofold: to test the presence of RAE depending on the gender and age in young alpine ski racers, and to test the influence of the level of physical motor skills on RAE. We investigated 989 participants of the entrance exams of three Austrian ski boarding schools, examined their birth dates and tested three different physical fitness abilities. Chi2-tests revealed significant RAEs for the total sample (Chi2=23.81; p<0.001**), as well as for participants of both genders, children aged 9-10 and adolescents aged 14-15 years. No gender or age specific differences were shown in relation to the extent of the RAE. The results indicate that the level of the tested physical motor skills does not influence the RAE. The selection at the entrance exams did not reveal RAEs; consequently, a substantial portion of the selection of relatively older athletes in the talent selection process has been completed before the entrance into a ski boarding school.